2011
DOI: 10.1111/j.1399-6576.2011.02533.x
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive tissue oxygen saturation determined by near‐infrared spectroscopy following peripheral nerve block

Abstract: Our results demonstrated sustained increases in tissue rSO(2) values following peripheral nerve block placement, in addition to higher initial rSO(2) values in operative limbs prior to block placement. Further investigations are necessary to define the expected baseline rSO(2) values in operative and control limbs. Future efforts utilizing NIRS-based detection of tissue ischemia should consider the small but significant changes in rSO(2) resulting from a successful nerve block.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 23 publications
0
25
0
Order By: Relevance
“…Therefore, PNB may enhance peripheral inflammation through the blockade of Nav1.8 following the incision, which is likely associated with infection. Another possibility is that the increase in tissue oxygen saturation by PNB 19 contributes to the increased infiltration of immune cells at the incision site. It was reported that the elevation of oxygen saturation by increased peripheral perfusion is correlated with the incidence of surgical site infection, 20 and promoted the migration of neutrophils through the induction of ICAM-1 expression on endothelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, PNB may enhance peripheral inflammation through the blockade of Nav1.8 following the incision, which is likely associated with infection. Another possibility is that the increase in tissue oxygen saturation by PNB 19 contributes to the increased infiltration of immune cells at the incision site. It was reported that the elevation of oxygen saturation by increased peripheral perfusion is correlated with the incidence of surgical site infection, 20 and promoted the migration of neutrophils through the induction of ICAM-1 expression on endothelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…We observed a significant increase in StO 2 after the onset of locoregional anesthesia. This was expected because brachial plexus block causes functional sympathectomy-like effects that lead to a complete vasodilatation and a subsequent increase in blood flow, microvascular arteriovenous shunting, and ultimately an increase in oxygen saturation [19,20].…”
mentioning
confidence: 99%
“…Others have demonstrated similar improvements in regional blood flow following peripheral nerve blockade using either Doppler flow or NIRS (14–16). Payen et al.…”
Section: Discussionmentioning
confidence: 97%
“…Additionally, given the limited magnitude of the change, it is unlikely that this technology can be used to document a successful block while under anesthesia. In comparison with the adult population, this may be due to the fact that pediatric patients have healthy vasculature as demonstrated by the fact that the baseline NIRS of the patients in the current of 82-83% is higher than those generally noted in the adult population (16). It is possible that the results may differ in the awake state during the postoperative period especially if there is stimulation of the sympathetic nervous system because of pain.…”
Section: The Link Between Tissue Oxygenation and Surgical Wound Infecmentioning
confidence: 90%
See 1 more Smart Citation